The Differential Effects of Auditors' Nonaudit and Audit Fees on Accrual Quality* - Srinidhi, Bin N.; Gul, Ferdinand A. (Contemporary Accounting Research, 2007)
This paper examines linkages between audit and nonaudit fees and accrual quality. We measure accrual quality by the Francis, Lafond, Olsson, and Schipper 2005 modification of the Dechow and Dichev 2002 measure. We posit that in settings where audit quality is compromised by a loss of auditor independence, managers use accruals more opportunistically and thereby drive down the accrual quality. Conversely, higher audit effort and quality translate to better accrual quality. Our dependent variables are the relative magnitude of nonaudit fees to audit fees and the absolute magnitudes of audit, nonaudit, and total fees. Results show that accrual quality has a significant negative association with the magnitude of nonaudit fees and a significant positive association with audit fees. This latter result is consistent with the proposition that higher audit fees reflect higher audit effort and better judgements about the propriety of accruals, but is not consistent with the proposition that audit fees are associated with economic bonding.